A method for preparing dicarboxylic acid and aniline by synergistic treatment of waste polyester and nitrobenzene

By using precious metal-supported catalysts to coordinate the treatment of polyester waste plastic and nitrobenzene under low temperature hydrothermal conditions, the treatment problem of polyester waste plastic and nitrobenzene wastewater is solved, and efficient high-value chemical recycling is achieved. Reduced environmental pollution and resource waste.

CN117645534BActive Publication Date: 2024-12-31ZHEJIANG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311362723.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-10-19
Publication Date
2024-12-31
Estimated Expiration
2043-10-19

AI Technical Summary

Technical Problem

The prior art is difficult to effectively treat polyester waste plastics and nitrobenzene wastewater, resulting in environmental pollution and waste of resources, and traditional recycling methods have high costs and secondary pollution problems.

Method used

The polyester waste plastic and nitrobenzene are used to coordinate the treatment of low temperature hydrothermal conditions by using precious metal-supported catalysts, and converted into high-value chemical dicarboxylic acid and aniline through one-step reaction, solving the problems of white pollution and wastewater treatment.

Benefits of technology

The rapid and high-value utilization of polyester waste plastics and nitrobenzene has been achieved, which reduces environmental pollution, improves resource recycling efficiency, and shows the catalyst characteristics of efficient, economical and multiple recycling.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117645534B_ABST
    Figure CN117645534B_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing dicarboxylic acid and aniline by synergistic treatment of waste polyester and nitrobenzene. The invention directly mixes polyester waste plastic, nitrobenzene and a noble metal-supported catalyst in a certain proportion and adds them to water, and uses the catalytic properties of the catalyst as a link to couple the hydrothermal depolymerization reaction of the polyester waste plastic and the in-situ redox reaction of the depolymerization product with nitrobenzene under specific hydrothermal conditions, and directly obtains dicarboxylic acid and aniline in a one-step method, while realizing high-value recycling of polyester waste plastic and nitrobenzene in wastewater. The catalyst has high catalytic efficiency in the reaction, is easy to separate and recycle, can be reused, and effectively reduces the reaction cost. In addition, the process is simple and ingenious, has low energy consumption, has extremely high industrial application value, and does not cause secondary pollution to the environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention also relates to the technical field of comprehensive utilization of waste resources and wastewater treatment, in particular to a method for coordinated treatment of solid waste and sewage. Background Art

[0002] Plastics have a wide range of uses and huge demand, and their production is increasing year by year. According to statistics, the global plastic production reached 360 million tons / year in 2021, and the cumulative production of plastic products has approached 10 billion tons / year. However, plastic products have a short life cycle, and most of them are discarded and become plastic waste after a single use. At present, most plastic waste is landfilled or directly incinerated, causing serious environmental pollution to the land, atmosphere, and oceans on which human beings depend for survival. Plastic pollution has become the world's second largest environmental issue after climate change; on the other hand, the large amount of carbon and hydrogen elements contained in waste plastics can partially replace fossil resources to prepare fuels and chemicals, and are valuable "urban minerals". Therefore, the resource utilization of waste plastics can directly reduce plastic waste and create value, turning waste into treasure, which is the most promising means of controlling plastic pollution.

[0003] Polyethylene terephthalate (PET) is the world's largest polyester plastic. Waste PET is one of the most common plastic wastes in domestic waste, accounting for about 10% of the total global plastic waste. Its difficult to degrade naturally has brought severe challenges to the ecological environment. At present, the recycling method of PET waste plastics in my country mostly adopts physical recycling, which has a low recycling value. The chemical recycling of PET is essentially the depolymerization reaction of PET, that is, under certain conditions, PET is completely degraded into monomers, such as terephthalic acid (TPA), ethylene glycol (EG), dimethyl terephthalate (DMT) or diethylene glycol terephthalate (BHET). Compared with the physical recycling method, the chemical method fully complies with the "sustainability" principle, preserves the molecular weight of the recycled PET waste, and can recycle contaminated and very complex waste streams into products of required specifications. However, the high-concentration alkaline solution used in the process will cause a large amount of waste liquid to be generated, and the EG produced at the same time is difficult to separate and recycle due to its high boiling point, and is usually abandoned. Therefore, how to utilize the structural characteristics of PET and explore an effective strategy that can couple PET solvolysis and in-situ directional upgrading of EG monomers, and simply and cleverly convert PET into high-value fuels and high-value chemicals is the only way to increase the comprehensive utilization value of PET waste plastics and quickly reduce their amount.

[0004] Nitrobenzene is widely used in the organic synthesis industry. It is an important fine chemical intermediate and raw material in the organic chemical industry. It is often used to produce products such as spices, explosives and dyes. However, nitrobenzene has high toxicity and very stable chemical properties. If nitrobenzene wastewater is discharged directly into the water without treatment, it will cause environmental pollution, which will endanger the ecological environment and human health. It has been listed as a priority pollutant by many countries. The common treatment methods for nitrobenzene wastewater are physical method, chemical oxidation method and biodegradation method, but these methods all have the problem of high cost or secondary pollution. In industry, the main use of nitrobenzene is to produce high-value chemical aniline by introducing a reducing agent. Aniline, as an important bulk chemical, is widely used in the production of rubber, dyes, pesticides, medicines, plastics, paints, etc. In industry, iron powder or hydrogen is generally used as the reducing agent for this reaction, but these reducing agents have disadvantages such as being harmful to the environment and having potential explosion risks, which restricts the production of aniline. EG, one of the PET depolymerization monomers, is a high-hydrogen organic compound with the potential to replace traditional reducing agents. Therefore, nitrobenzene can be captured by the EG component from the PET depolymerization monomer, thereby solving the EG separation problem and realizing the utilization of hydrogen energy in EG. This high-value recovery strategy is conducive to the comprehensive utilization of PET waste at the molecular level, which helps to alleviate the consumption of petroleum resources to a certain extent and improve the recycling value of PET waste. Summary of the invention

[0005] The present invention aims at the directional upgrading demand of polyester waste plastics and the bottleneck of nitrobenzene treatment in wastewater, and proposes a method for preparing dicarboxylic acid and aniline by synergistic treatment of waste polyester and nitrobenzene, which can solve the problems of white pollution and wastewater treatment at the same time in a low-temperature hydrothermal environment, and directional preparation of high-value chemicals dicarboxylic acid and aniline. The present invention has a simple process flow and high economic benefits, realizes the clean and high-value utilization of polyester waste plastics and nitrobenzene, and reduces the potential negative impact of waste plastic and wastewater treatment processes on the environment.

[0006] The specific technical solutions adopted by the present invention are as follows:

[0007] A method for preparing dicarboxylic acid and aniline by synergistic treatment of waste polyester and nitrobenzene, the specific steps of which are: polyester waste plastic, nitrobenzene and a noble metal-supported catalyst are mixed and added into water to form a reaction system; under hydrothermal conditions, a hydrothermal depolymerization reaction of the polyester waste plastic and an in-situ redox reaction of nitrobenzene are coupled, so that the reactants in the reaction system are completely converted in one step to directly obtain dicarboxylic acid and aniline; the noble metal-supported catalyst is a Ru, Pt, Pd, or Rh-based supported catalyst obtained after hydrogen reduction calcination treatment.

[0008] Preferably, the molar ratio of the added amount of nitrobenzene to the polyester material is 1:(0.6-1), preferably 1:0.6.

[0009] Preferably, the amount of the noble metal supported catalyst added is 0.5 wt% to 5 wt% of the polyester material, preferably 2 wt%.

[0010] Preferably, the amount of water added to the reaction system is 1-5 mL / mmol of polyester material, preferably 3 mL / mmol of polyester material.

[0011] Preferably, the polyester material is polyethylene terephthalate (PET), polyethylene adipate or polyethylene succinate; preferably, it is waste made of polyethylene terephthalate, and the waste needs to be pre-crushed into centimeter-level flakes, particles or powder before adding it to the reactor, which can ensure the resource utilization effect of waste PET materials and obtain terephthalic acid and aniline in a targeted manner with high yield.

[0012] Preferably, the waste is in the form of PET waste bottles, PET matrix waste films, PET colored bundles or PET non-woven fabrics.

[0013] Preferably, in the hydrothermal conditions, the reaction temperature is 180-300° C., and the reaction time is 6-48 h; more preferably, the reaction temperature is 225° C., and the reaction time is 24 h.

[0014] Preferably, the preparation method of the noble metal supported catalyst is: mixing a soluble salt of the noble metal and a carrier in water according to a ratio, then drying and removing the solvent to obtain a solid sample, grinding the solid sample into powder and placing it in an argon gas flow containing hydrogen, and performing hydrogen reduction calcination treatment at 450-500°C for 4-8h to obtain a noble metal supported catalyst after calcination; the noble metal is Ru, Pt, Pd or Rh, and the noble metal content in the noble metal supported catalyst is 0.2wt.%-10wt.%.

[0015] Preferably, the soluble salt of the noble metal is ruthenium trichloride, rhodium trichloride, platinum tetrachloride, or palladium nitrate hydrate; and the carrier is a molecular sieve, a metal oxide, or activated carbon.

[0016] Preferably, in the hydrogen reduction calcination treatment, the powdered solid sample is ground into a tubular furnace, first heated to 450°C in an argon flow containing 5% hydrogen and maintained for 4 hours, then heated to 500°C in an argon flow containing 5% hydrogen and maintained for 4 hours, and then cooled to obtain the precious metal supported catalyst.

[0017] Preferably, the noble metal-supported catalyst is a Ru-supported anatase catalyst, that is, in the catalyst, the noble metal is Ru and the carrier is anatase.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] (1) The present invention provides a method for preparing dicarboxylic acid and aniline by co-processing waste polyester and nitrobenzene, which realizes the one-step rapid processing of PET polyester waste plastics and nitrobenzene in wastewater, and obtains high-value products.

[0020] (2) The noble metal-supported catalyst used in the present invention has the advantages of high efficiency, simple recovery, and multiple recycling, and can promote the hydrolysis reaction of PET and the directional upgrading and recovery of EG in a relatively short time.

[0021] (3) The method provided by the present invention for preparing dicarboxylic acid and aniline by synergistic treatment of waste polyester and nitrobenzene can achieve excellent results of 99% yield of terephthalic acid, 95% yield of aniline, and 100% selectivity of aniline. Moreover, the strategy has a wide range of applications, and the types of waste PET raw materials are varied. Various types of waste PET materials, such as various types of PET waste bottles, PET matrix waste films, PET colored ropes and PET non-woven fabrics, can all be efficiently upgraded and converted in a short time.

[0022] (4) The PET waste plastic matrix material of the present invention can be replaced by various polyesters having similar diol units, such as polyethylene succinate and polyethylene adipate, which to a certain extent demonstrates the high applicability of the strategy and further broadens the scope of waste plastic treatment materials. Under the premise of ensuring high depolymerization efficiency and rapid reaction time, the corresponding conversion to obtain dicarboxylic acids and aniline can be completed. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a demonstration of the catalyst recycling effect in the embodiments of the present invention. DETAILED DESCRIPTION

[0024] In order to make the above-mentioned purpose, features and advantages of the present invention more obvious and easy to understand, the following is a detailed description through specific embodiments. In the following description, many specific details are set forth in order to fully understand the present invention. However, the present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed below. The technical features in each embodiment of the present invention can be combined accordingly without conflicting with each other.

[0025] In the following embodiment of the present invention, a method for preparing dicarboxylic acid and aniline by co-processing waste polyester and nitrobenzene is provided, and the specific steps thereof include:

[0026] S1. Put crushed polyester material, nitrobenzene, noble metal supported catalyst and water solvent in a reaction kettle; wherein the polyester material is polyethylene terephthalate (PET), polyethylene adipate or polyethylene succinate. In addition, the molar ratio of nitrobenzene to polyester material is 1:(0.6-1), the amount of noble metal supported catalyst added is 0.5wt%-5wt% of polyester material, and the amount of water added is 1-5mL / mmol of polyester material.

[0027] S2. Place the above reactor at a depolymerization temperature of 180-300°C for 6-48h of hydrothermal depolymerization reaction. In this reaction process, with the catalytic properties of the catalyst as the link, under specific hydrothermal conditions, the hydrothermal depolymerization reaction of polyester waste plastics and the in-situ redox reaction of nitrobenzene are coupled, so that the reactants in the reaction system (polyester materials, nitrobenzene) are directly converted into dicarboxylic acid monomers and aniline through one-step complete conversion. After the above reaction is completed, it is cooled to room temperature to obtain products containing high-value dicarboxylic acid monomers and aniline, realizing the high-value recycling of polyester waste plastics and nitrobenzene in wastewater.

[0028] The present invention can be used for depolymerization and upgrading of waste PET materials, and can also be used for other similar polyesters, such as polyethylene adipate and polyethylene succinate, which are also suitable for the recycling strategy of the present invention, and the products are aniline and the corresponding dicarboxylic acid monomers. Taking PET materials as an example, the products are terephthalic acid and aniline.

[0029] It should be noted that the catalyst in the present invention must be a Ru, Pt, Pd, or Rh-based supported catalyst. However, the type of carrier can be regulated to change the catalytic performance, such as various types of molecular sieves, metal oxides, activated carbon, etc. The test shows that the anatase carrier can achieve the best depolymerization reaction performance. The preparation method of the noble metal supported catalyst can be implemented in the following manner: the soluble salt of the noble metal and the carrier are mixed in water according to a ratio, and then the solid sample is dried at room temperature to remove the solvent to obtain a solid sample, and the solid sample is ground into a powder and placed in an argon gas flow containing hydrogen, and a hydrogen reduction roasting treatment is performed at 450 to 500° C. for 4 to 8 hours, and a noble metal supported catalyst is obtained after the roasting treatment. The aforementioned noble metal soluble salt is a soluble salt of Ru, Pt, Pd, or Rh, such as ruthenium trichloride, rhodium trichloride, platinum tetrachloride, palladium nitrate hydrate, and the noble metal content in the noble metal supported catalyst is 0.2wt.% to 10wt.%.

[0030] Referring to Examples 1 to 20, examples of application of the one-step conversion process to common polyester waste plastics are as follows:

[0031] Example 1

[0032] Preparation of ruthenium-loaded anatase catalyst: In a 25mL beaker, add 1g of anatase and 0.0311g (0.15mmol) of ruthenium trichloride respectively and dissolve in 5g of deionized water. After dissolution, ultrasonicate for 40min to mix evenly, place in a fume hood to dry at room temperature, grind the dried sample into powder and then perform hydrogen reduction calcination treatment, specifically: place the sample powder in a tubular furnace, first heat to 450°C in an argon flow containing 5% hydrogen and maintain for 4h, then heat to 500°C in an argon flow containing 5% hydrogen and maintain for another 4h. The catalyst obtained after calcination is the ruthenium-loaded anatase catalyst (Ru-TiO2).

[0033] Catalytic performance test: 0.115g PET powder (0.6mmol), 102.6μL nitrobenzene (1mmol), 0.1g Ru-TiO2 after reduction roasting and 4mL water were added to an autoclave reactor equipped with an electromagnetic stirrer, a thermocouple and a programmable temperature controller. After placing the autoclave reactor, stirring and heating were turned on. The reaction system was heated to 225°C and reacted at this temperature for 24h. After the reaction was completed, the temperature was lowered to room temperature, and the obtained mixed solution was the product. The obtained mixed solution was extracted with dichloromethane, and the extract was measured by GC for yield, with dodecane as the internal standard. The results showed that the PET decomposition rate of this embodiment was 100%, the terephthalic acid yield was 99%, and the aniline yield was 95%.

[0034] Example 2

[0035] The catalyst preparation method is the same as in Example 1.

[0036] Catalytic performance test: The discarded PET plastic bottles (Nongfu Spring) were crushed at the centimeter level in advance, and then 0.115g of the centimeter-level crushed material of the PET plastic bottles (0.6mmol), 102.6μL nitrobenzene (1mmol), 0.1g of Ru-TiO2 after reduction roasting and 4mL of water were added to an autoclave reactor equipped with an electromagnetic stirrer, a thermocouple, and a program temperature controller. After placing the autoclave reactor, stirring and heating were turned on. The reaction system was heated to 225°C and reacted at this temperature for 24h. After the reaction was completed, it was cooled to room temperature, and the resulting mixed solution was the product. The resulting mixed solution was diluted with dichloromethane, and the diluent was measured for yield by GC, with dodecane as the internal standard. The results showed that the PET decomposition rate of this embodiment was 100%, the terephthalic acid yield was 99%, and the aniline yield was 96%.

[0037] Example 3

[0038] The catalyst preparation method is the same as in Example 1.

[0039] Catalytic performance test: add 0.172g polyethylene adipate (1mmol), 102.6μL nitrobenzene (1mmol), 0.1g Ru-TiO2 after reduction roasting and 4mL water in an autoclave reactor equipped with an electromagnetic stirrer, a thermocouple and a program temperature controller, and after placing the autoclave reactor, open stirring and heating. The reaction system is warming up to 225 ℃, and reacts at this temperature for 24h. After the reaction is completed, cool to room temperature, and the obtained mixed solution is the product. The obtained mixed solution is diluted with dichloromethane, and the diluent is measured by GC to determine the yield, and dodecane is used as an internal standard. The result shows that the polyethylene adipate decomposition rate of the present embodiment is 100%, the adipic acid yield is 98%, and the yield of aniline is 91%.

[0040] Example 4

[0041] The catalyst preparation method is the same as in Example 1.

[0042] Catalytic performance test: add 0.144g polyethylene succinate (1mmol), 102.6μL nitrobenzene (1mmol), 0.1g Ru-TiO2 after reduction roasting and 4mL water in an autoclave reactor equipped with an electromagnetic stirrer, a thermocouple and a program temperature controller, and after placing the autoclave reactor, open stirring and heating. The reaction system is warmed up to 225 ℃, and reacts at this temperature for 24h. After the reaction is completed, cool to room temperature, and the obtained mixed solution is the product. The obtained mixed solution is diluted with dichloromethane, and the diluent is measured by GC to determine the yield, and dodecane is used as an internal standard. The result shows that the decomposition rate of polyethylene succinate of the present embodiment is 100%, the yield of succinic acid is 98%, and the yield of aniline is 93%.

[0043] Referring to Examples 1 and 5-13, the effects of different active metals and different carriers on the one-step conversion of PET polyester waste plastics are as follows:

[0044] Example 5

[0045] Preparation of rhodium-loaded anatase catalyst: Preparation of heterogeneous catalyst rhodium-loaded anatase: In a 25mL beaker, add 1g of anatase and 0.0395g (0.15mmol) of rhodium trichloride hydrate respectively and dissolve them in 5g of deionized water. After dissolution, ultrasonicate for 40min to mix it evenly, place it in a fume hood and dry it at room temperature. After grinding the dried sample into powder, it is subjected to hydrogen reduction calcination treatment, specifically: the sample powder is placed in a tubular furnace, first heated to 450°C in an argon flow containing 5% hydrogen and maintained for 4h, then heated to 500°C in an argon flow containing 5% hydrogen and maintained for another 4h. The catalyst obtained after calcination is the rhodium-loaded anatase catalyst (Rh-TiO2).

[0046] Catalytic performance test: 0.115g PET powder (0.6mmol), 102.6μL nitrobenzene (1mmol), 0.1g Rh-TiO2 after reduction roasting and 4mL water were added to an autoclave reactor equipped with an electromagnetic stirrer, a thermocouple and a program temperature controller. After placing the autoclave reactor, stirring and heating were turned on. The reaction system was heated to 225°C and reacted at this temperature for 24h. After the reaction was completed, the temperature was lowered to room temperature, and the obtained mixed solution was the product. The obtained mixed solution was diluted with dichloromethane, and the diluent was measured by GC for yield, with dodecane as the internal standard. The results showed that the PET decomposition rate of the present embodiment was 100%, the terephthalic acid yield was 99%, and the yield of aniline was 93%.

[0047] Example 6

[0048] Preparation of platinum-loaded anatase catalyst: Preparation of heterogeneous catalyst platinum-loaded anatase: In a 25mL beaker, add 1g of anatase and 0.0504g (0.15mmol) of platinum tetrachloride respectively and dissolve in 5g of deionized water. After dissolution, ultrasonicate for 40min to mix evenly, place in a fume hood and dry at room temperature. After grinding the dried sample into powder, perform hydrogen reduction calcination treatment. Specifically, place the sample powder in a tubular furnace, first heat to 450°C in an argon flow containing 5% hydrogen and maintain for 4h, then heat to 500°C in an argon flow containing 5% hydrogen and maintain for another 4h. The catalyst obtained after calcination is the platinum-loaded anatase catalyst (Pt-TiO2).

[0049] Catalytic performance test: 0.115g PET powder (0.6mmol), 102.6μL nitrobenzene (1mmol), 0.1g Pt-TiO2 after reduction roasting and 4mL water were added to an autoclave reactor equipped with an electromagnetic stirrer, a thermocouple and a program temperature controller. After placing the autoclave reactor, stirring and heating were turned on. The reaction system was heated to 225°C and reacted at this temperature for 24h. After the reaction was completed, the temperature was lowered to room temperature, and the obtained mixed solution was the product. The obtained mixed solution was diluted with dichloromethane, and the diluent was measured by GC for yield, with dodecane as the internal standard. The results showed that the PET decomposition rate of the present embodiment was 100%, the terephthalic acid yield was 99%, and the yield of aniline was 86%.

[0050] Example 7

[0051] Preparation of palladium-supported anatase catalyst: Preparation of heterogeneous catalyst palladium-supported anatase: In a 25mL beaker, add 1g of anatase and 0.040g (0.15mmol) of palladium nitrate hydrate respectively and dissolve them in 5g of deionized water. After dissolution, ultrasonicate for 40min to mix it evenly, place it in a fume hood and dry it at room temperature. After grinding the dried sample into powder, it is subjected to hydrogen reduction calcination treatment. Specifically, the sample powder is placed in a tubular furnace, first heated to 450°C in an argon flow containing 5% hydrogen and maintained for 4h, then heated to 500°C in an argon flow containing 5% hydrogen and maintained for another 4h. The catalyst obtained after calcination is the palladium-supported anatase catalyst (Pd-TiO2).

[0052] Catalytic performance test: 0.115g PET powder (0.6mmol), 102.6μL nitrobenzene (1mmol), 0.1g Pd-TiO2 after reduction roasting and 4mL water were added to an autoclave reactor equipped with an electromagnetic stirrer, a thermocouple and a program temperature controller. After placing the autoclave reactor, stirring and heating were turned on. The reaction system was heated to 225°C and reacted at this temperature for 24h. After the reaction was completed, the temperature was lowered to room temperature, and the obtained mixed solution was the product. The obtained mixed solution was diluted with dichloromethane, and the diluent was measured by GC for yield, with dodecane as the internal standard. The results showed that the PET decomposition rate of the present embodiment was 100%, the terephthalic acid yield was 99%, and the yield of aniline was 92%.

[0053] Referring to Examples 1 and 8-13, the effects of different carriers on the one-step conversion of PET polyester waste plastics are as follows:

[0054] Example 8

[0055] Preparation of ruthenium-loaded TS-1 catalyst: In a 25mL beaker, add 1g of TS-1 and 0.0311g (0.15mmol) of ruthenium trichloride respectively and dissolve in 5g of deionized water. After dissolution, ultrasonicate for 40min to mix evenly, place in a fume hood to dry at room temperature, grind the dried sample into powder and then perform hydrogen reduction calcination treatment. Specifically, place the sample powder in a tubular furnace, first heat to 450°C in an argon flow containing 5% hydrogen and maintain for 4h, then heat to 500°C in an argon flow containing 5% hydrogen and maintain for another 4h. The catalyst obtained after calcination is the ruthenium-loaded TS-1 catalyst (Ru-TS-1).

[0056] Catalytic performance test: 0.115g PET powder (0.6mmol), 102.6μL nitrobenzene (1mmol), 0.1g Ru-TS-1 and 4mL water were added to an autoclave reactor equipped with an electromagnetic stirrer, a thermocouple and a programmable temperature controller. After the autoclave reactor was placed, stirring and heating were turned on. The reaction system was heated to 225°C and reacted at this temperature for 24h. After the reaction was completed, the temperature was cooled to room temperature, and the resulting mixed solution was the product. The resulting mixed solution was diluted with dichloromethane, and the diluent was measured for yield by GC, with dodecane as the internal standard. The results showed that the PET decomposition rate of this embodiment was 100%, the terephthalic acid yield was 99%, and the aniline yield was 27%.

[0057] Example 9

[0058] Ruthenium-loaded S-1 catalyst: In a 25mL beaker, add 1g of S-1 and 0.0311g (0.15mmol) of ruthenium trichloride respectively and dissolve in 5g of deionized water. After dissolution, ultrasonicate for 40min to mix evenly, place in a fume hood to dry at room temperature, grind the dried sample into powder and then perform hydrogen reduction calcination treatment. Specifically, place the sample powder in a tubular furnace, first heat to 450°C in an argon flow containing 5% hydrogen and maintain for 4h, then heat to 500°C in an argon flow containing 5% hydrogen and maintain for another 4h. The catalyst obtained after calcination is the ruthenium-loaded S-1 catalyst (Ru-S-1).

[0059] Catalytic performance test: 0.115g PET powder (0.6mmol), 102.6μL nitrobenzene (1mmol), 0.1g Ru-S-1 and 4mL water were added to an autoclave reactor equipped with an electromagnetic stirrer, a thermocouple and a programmable temperature controller. After the autoclave reactor was placed, stirring and heating were turned on. The reaction system was heated to 225°C and reacted at this temperature for 24h. After the reaction was completed, the temperature was cooled to room temperature, and the resulting mixed solution was the product. The resulting mixed solution was diluted with dichloromethane, and the diluent was measured for yield by GC, with dodecane as the internal standard. The results showed that the PET decomposition rate of this embodiment was 100%, the terephthalic acid yield was 99%, and the aniline yield was 38%.

[0060] Example 10

[0061] Preparation of ruthenium-loaded ZSM-5 catalyst: In a 25mL beaker, add 1g of ZSM-5 and 0.0311g (0.15mmol) of ruthenium trichloride respectively and dissolve in 5g of deionized water. After dissolution, ultrasonicate for 40min to mix evenly, place in a fume hood to dry at room temperature, grind the dried sample into powder and then perform hydrogen reduction calcination treatment. Specifically, place the sample powder in a tubular furnace, first heat to 450°C in an argon flow containing 5% hydrogen and maintain for 4h, then heat to 500°C in an argon flow containing 5% hydrogen and maintain for another 4h. The catalyst obtained after calcination is the ruthenium-loaded ZSM-5 catalyst (Ru-ZSM-5).

[0062] Catalytic performance test: 0.115g PET powder (0.6mmol), 102.6μL nitrobenzene (1mmol), 0.1g Ru-ZSM-5 and 4mL water were added to an autoclave reactor equipped with an electromagnetic stirrer, a thermocouple and a program temperature controller. After the autoclave reactor was placed, stirring and heating were turned on. The reaction system was heated to 225°C and reacted at this temperature for 24h. After the reaction was completed, the temperature was cooled to room temperature, and the resulting mixed solution was the product. The resulting mixed solution was diluted with dichloromethane, and the diluent was measured by GC for yield, with dodecane as the internal standard. The results showed that the PET decomposition rate of this embodiment was 100%, the terephthalic acid yield was 99%, and the aniline yield was 33%.

[0063] Embodiment 11

[0064] Preparation of ruthenium-loaded activated carbon catalyst: In a 25mL beaker, add 1g of activated carbon and 0.0311g (0.15mmol) of ruthenium trichloride respectively and dissolve in 5g of deionized water. After dissolution, ultrasonicate for 40min to mix evenly, place in a fume hood to dry at room temperature, grind the dried sample into powder and then perform hydrogen reduction calcination treatment. Specifically, place the sample powder in a tubular furnace, first heat to 450°C in an argon flow containing 5% hydrogen and maintain for 4h, then heat to 500°C in an argon flow containing 5% hydrogen and maintain for another 4h. The catalyst obtained after calcination is the ruthenium-loaded activated carbon catalyst (Ru-C).

[0065] Catalytic performance test: 0.115g PET powder (0.6mmol), 102.6μL nitrobenzene (1mmol), 0.1g Ru-C and 4mL water were added to an autoclave reactor equipped with an electromagnetic stirrer, a thermocouple and a programmable temperature controller. After the autoclave reactor was placed, stirring and heating were turned on. The reaction system was heated to 225°C and reacted at this temperature for 24h. After the reaction was completed, the temperature was lowered to room temperature, and the resulting mixed solution was the product. The resulting mixed solution was diluted with dichloromethane, and the diluent was measured for yield by GC, with dodecane as the internal standard. The results showed that the PET decomposition rate of this embodiment was 100%, the terephthalic acid yield was 99%, and the aniline yield was 67%.

[0066] Embodiment 13

[0067] Preparation of ruthenium-loaded CeO2 catalyst: In a 25mL beaker, add 1g of CeO2 and 0.0311g (0.15mmol) of ruthenium trichloride respectively and dissolve in 5g of deionized water. After dissolution, ultrasonicate for 40min to mix evenly, place in a fume hood to dry at room temperature, grind the dried sample into powder and then perform hydrogen reduction calcination treatment. Specifically, place the sample powder in a tubular furnace, first heat to 450°C in an argon flow containing 5% hydrogen and maintain for 4h, then heat to 500°C in an argon flow containing 5% hydrogen and maintain for another 4h. The catalyst obtained after calcination is the ruthenium-loaded CeO2 catalyst (Ru-CeO2).

[0068] Catalytic performance test: 0.115g PET powder (0.6mmol), 102.6μL nitrobenzene (1mmol), 0.1g Ru-CeO2 and 4mL water were added to an autoclave reactor equipped with an electromagnetic stirrer, a thermocouple and a programmable temperature controller. After the autoclave reactor was placed, stirring and heating were turned on. The reaction system was heated to 225°C and reacted at this temperature for 24h. After the reaction was completed, the temperature was lowered to room temperature, and the resulting mixed solution was the product. The resulting mixed solution was diluted with dichloromethane, and the diluent was measured for yield by GC, with dodecane as the internal standard. The results showed that the PET decomposition rate of this embodiment was 100%, the terephthalic acid yield was 99%, and the aniline yield was 36%.

[0069] Embodiment 14

[0070] This example tests the recycling of catalyst:

[0071] The catalyst preparation method and catalytic performance test are the same as in Example 1.

[0072] In order to prove the recyclability of the catalyst in the present invention, the ruthenium-loaded anatase catalyst Ru-TiO2 was separated and recovered after the reaction, and after rinsing and impurity removal, it was dried at 150°C, and the obtained catalyst was directly recycled to the next reaction. Figure 1 As shown, after repeated use for 10 times, the yields of terephthalic acid and aniline still reached 99% and 93%, respectively.

[0073] Examples 15-20

[0074] The following examples investigate the reaction temperature:

[0075] The preparation method of the ruthenium-supported anatase catalyst Ru-TiO2 and the basic catalytic performance test are the same as those in Example 1, except that the reaction temperature in the hydrothermal condition is changed to 180 / 200 / 225 / 240 / 270 / 300°C, corresponding to Examples 15-20, respectively. The reaction results are shown in Table 1.

[0076] Table 1

[0077]

[0078] Examples 21-25

[0079] The following examples investigate the reaction time:

[0080] The preparation method of the ruthenium-supported anatase catalyst Ru-TiO2 and the catalytic performance test are the same as those in Example 1, except that the reaction time in the hydrothermal condition is changed to 6 / 12 / 18 / 24 / 48 h, corresponding to Examples 21-25, respectively. The reaction results are shown in Table 2.

[0081] Table 2

[0082]

[0083] The above-described embodiment is only a preferred solution of the present invention, but it is not intended to limit the present invention. A person skilled in the relevant technical field may make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, any technical solution obtained by equivalent replacement or equivalent transformation falls within the protection scope of the present invention.

Claims

1. A method for preparing dicarboxylic acid and aniline by synergistic treatment of waste polyester and nitrobenzene, characterized in that: Polyester waste plastics, nitrobenzene and a precious metal-loaded catalyst are mixed and added into water to form a reaction system. Under hydrothermal conditions, the hydrothermal depolymerization reaction of the polyester waste plastics and the in-situ redox reaction of nitrobenzene are coupled so that the reactants in the reaction system are completely converted in one step to directly obtain dicarboxylic acids and aniline. The polyester waste plastics are waste materials made of polyethylene terephthalate, polyethylene adipate or polyethylene succinate; the precious metal-loaded catalyst is a Ru, Pt, Pd or Rh-based loaded catalyst obtained after hydrogen reduction calcination treatment, and the carrier is a molecular sieve, a metal oxide or activated carbon.

2. The method for preparing dicarboxylic acid and aniline by synergistic treatment of waste polyester and nitrobenzene as claimed in claim 1, characterized in that: The molar ratio of the added amount of nitrobenzene to the polyester waste plastic is 1:(0.6-1).

3. The method for preparing dicarboxylic acid and aniline by synergistic treatment of waste polyester and nitrobenzene as claimed in claim 1, characterized in that: The amount of the noble metal supported catalyst added is 0.5 wt% to 5 wt% of the polyester waste plastic.

4. The method for preparing dicarboxylic acid and aniline by synergistic treatment of waste polyester and nitrobenzene as claimed in claim 1, characterized in that: The amount of water added to the reaction system is 1-5 mL / mmol of polyester waste plastic.

5. The method for preparing dicarboxylic acid and aniline by synergistic treatment of waste polyester and nitrobenzene as claimed in claim 1, characterized in that: The polyester waste plastic is waste made of polyethylene terephthalate, and the waste needs to be broken into centimeter-level flakes, particles or powder before being added into the reactor.

6. The method for preparing dicarboxylic acid and aniline by synergistic treatment of waste polyester and nitrobenzene as claimed in claim 1, characterized in that: The waste is in the form of polyethylene terephthalate waste bottles, polyethylene terephthalate matrix waste films, polyethylene terephthalate colored bundles or polyethylene terephthalate non-woven fabrics.

7. The method for preparing dicarboxylic acid and aniline by synergistic treatment of waste polyester and nitrobenzene as claimed in claim 1, characterized in that: In the hydrothermal conditions, the reaction temperature is 180-300°C and the reaction time is 6-48 h.

8. The method for preparing dicarboxylic acid and aniline by co-processing waste polyester and nitrobenzene as claimed in claim 1, characterized in that: The preparation method of the noble metal supported catalyst is as follows: a soluble salt of the noble metal and a carrier are mixed in water according to a proportion, and then a solid sample is obtained after drying to remove the solvent, and the solid sample is ground into powder and placed in an argon gas flow containing hydrogen, and a hydrogen reduction calcination treatment is performed at 450-500° C. for 4-8 h to obtain a noble metal supported catalyst; the noble metal is Ru, Pt, Pd or Rh, and the noble metal content in the noble metal supported catalyst is 0.2 wt.%-10wt.%.

9. The method for preparing dicarboxylic acid and aniline by synergistic treatment of waste polyester and nitrobenzene as claimed in claim 8, characterized in that: The soluble salt of the noble metal is ruthenium trichloride, rhodium trichloride, platinum tetrachloride, and palladium nitrate hydrate.

10. The method for preparing dicarboxylic acid and aniline by co-processing waste polyester and nitrobenzene as claimed in claim 8, characterized in that: In the hydrogen reduction calcination treatment, the powdered solid sample is ground and placed in a tubular furnace, first heated to 450°C in an argon flow containing 5% hydrogen and maintained for 4 hours, then heated to 500°C in an argon flow containing 5% hydrogen and maintained for 4 hours, and then cooled to obtain the noble metal supported catalyst.

11. The method for preparing dicarboxylic acid and aniline by co-processing waste polyester and nitrobenzene as claimed in claim 10, characterized in that: In the noble metal supported catalyst, the noble metal is Ru and the carrier is anatase.